(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Memecylon malabaricum (C.B.Clarke) Cogn. belongs to the family Melastomataceae is one of the important medicinal plants in traditional system of medicine. It has been used to treat diabetes, bacterial infections, and skin disorders including Herpes. Hence, the present study deals with the analysis of stem and leaf extracts through GC-MS to identify the bioactive compounds. 29 in stem and 25 phytochemicals in leaf extract were identified. Based on the results of GC-MS analysis further studies were carried out to estimate phenols, flavonoids and total antioxidant activity. It was found that stem methanolic extract has slightly more quantity of phenolics than the leaf extract. However, leaf extract has shown a considerable amount of flavonoids and better antioxidant activity than stem extract as revealed by DPPH, ABTS and reducing power assay. Further, inhibition of the activity of α-amylase by leaf extract was detected through preliminary studies thereby supporting its traditional use to treat diabetes.